Numerical study on the rotation capacity of SIP-strengthened cold-formed steel beams. (15th January 2022) - Shawki Osman, Hussein; Serror, Mohammed H.; Fathallah, Elsayed
Graphical abstract: Highlights: Using SIP with CFS beam exhibits improvements in beam strength, rotation capacity and initial stiffness. The increasing in SIP dimensions improves the strength and rotation capacity of the beam. The proposed detailing (CONFIG-1 and CONFIG-2) can be applied to enhance the strength and ductility of MRF connections. Two pairs of vertical stiffeners are needed in addition to the SIP to improve the overall behavior. Abstract: The use of cold-formed steel (CFS) beams in moment-resisting frames (MRFs) has recently become a topic of interest to many researchers. In this research, a numerical study has been performed to investigate an innovative seismic protection system and new energy dissipation technique called steel interconnected part (SIP), to allow CFS to be used in regions with high seismic activity. Through this technique, a steel part has been connected to 2C-channel back-to-back CFS beams to improve both strength and structural behavior. The steel part does not require much space because of its shape, which can be easily connected to the CFS beams. Finite element procedure in ABAQUS has been used to model the 2C-channel back-to-back connected with a through plate by bolts. In this paper, a total of 240 models have been studied under monotonic loading and 27 models under cyclic loading. The rotation capacity of CFS beams strengthened with SIP has been reported with different through plate dimensions. Different beam profile slenderness ratios with different geometric configurations for SIP have been studied. In the CFS beams without SIP, early loss of strength has been observed with premature flange and web buckling. The results revealed that the beams are strengthened using SIP can delay local failures and improve strength, initial stiffness, ductility and energy dissipation behavior, which cannot be attained by conventional CFS elements and connections. The proposed SIP system revealed promising results, that could achieve all the desired performance objectives and satisfy the requirements of common seismic codes.